BMI self-selection: Exploring alternatives to self-reported BMI. Issue 3 (July 2021) - Shiely, Frances; Millar, Seán R
Background: Accurately measuring BMI in large epidemiological studies is problematic as objective measurements are expensive, so subjective methodologies must usually suffice. The purpose of this study is to explore a new subjective method of BMI measurement: BMI self-selection. Methods: A cross-sectional analysis of the Mitchelstown Cohort Rescreen study, a random sample of 1, 354 men and women aged 51–77 years recruited from a single primary care centre. BMI self-selection was measured by asking patients to select their BMI category: underweight, normal weight, overweight, obese. Weight and height were also objectively measured. Results: 79% were overweight or obese: 86% of males, 69% of females (P < 0.001) and 59% of these underestimated their BMI. The sensitivity for correct BMI self-selection for normal weight, overweight and obese was 77%, 61% and 11% respectively. In multivariable analysis, gender, higher education levels, being told by a health professional to lose weight, and being on a diet were significantly associated with correct BMI self-selection. There was a linear trend relationship between increasing BMI levels and correct selection of BMI; participants in the highest BMI quartile had an approximate eight-fold increased odds of correctly selecting their BMI when compared to participants within the lower overweight/obese quartiles (OR = 7.72, 95%CI:4.59, 12.98). Conclusions: BMI self-selection may be useful for self-reporting BMI. Clinicians need to be aware of disparities between BMI self-selection at higher and lower BMI levels among overweight/obese patients and encourage preventative action for those at the lower levels to avoid weight gain and thus reduce their all-cause mortality risk.